A birth cohort analysis of the incidence of adenocarcinoma of the uterine cervix in the USA. Issue 3 (May 2015) - Zhu, Cairong; Bassig, Bryan A.; Zhang, Yawei; Shi, Kunchong; Boyle, Peter; Li, Ni; Zheng, Tongzhang
Abstract : We investigated the incidence trends for adenocarcinoma (AC) of the cervix among individuals belonging to the 20–44-year age group in the USA and compared the observed birth cohort incidence patterns with the changing patterns of exposure to potential risk factors associated with AC of the cervix, such as infection with human papillomavirus, use of diethylstilbestrol (DES), obesity, and use of oral contraceptives. Using data from the National Cancer Institute's Surveillance, Epidemiology, and End Results program for 1973–2010, we conducted age–period–cohort modeling to evaluate birth cohort patterns on incidence trends of AC of the cervix over time. The increase in the incidence of AC of the cervix started among those born around the mid 1940s and accelerated up until around the mid 1960s birth cohort in both whites and all races combined, regardless of the assumed period slope. There was a suggestion that the incidence rates of AC of the cervix slowed down after the 1975 birth cohort in both whites and all races combined. DES was used by millions of women in the USA as a synthetic estrogen between the years 1940 and 1971. This time period of DES use among pregnant women parallels the observed birth cohort trends in our study, whereby a notable acceleration in the incidence rates of AC of the cervix was observed among those born in the mid 1940s through the mid 1975s. Thus, our results appear to suggest that in-utero exposure to DES might be at least partly responsible for the observed incidence pattern of AC of the cervix as observed in this study.